1991
DOI: 10.1111/j.1365-2230.1991.tb00395.x
|View full text |Cite
|
Sign up to set email alerts
|

An immunological study in patients with seborrhoeic dermatitis

Abstract: The humoral and cellular immune-status was studied in 30 patients with seborrhoeic dermatitis. Increased frequencies of natural killer cells were found in 46% of patients. Furthermore, subnormal mitogen stimulation responses were demonstrated in 13 patients, whereas two individuals were found to have very high numbers of activated T lymphocytes in peripheral blood. Higher-than-normal total serum IgG and IgA was observed in 14 and 11 patients, respectively. For nine of 12 patients with skin lesions, dermal peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 26 publications
1
42
0
1
Order By: Relevance
“…An early histological study of SD demonstrated the presence of lymphocytes within lesions (335), and this was confirmed later when they were identified as mainly Th CD4-positive cells (51). Langerhans' cell numbers were not increased in lesional skin, and HLA-DR expression on keratinocytes was noted only infrequently (51). An extensive study recently found the infiltrate to consist of lymphocytes, macrophages, monocytes, and Langerhans' cells, with a few granulocytes (131).…”
Section: Cellular Immune Responsesmentioning
confidence: 89%
See 1 more Smart Citation
“…An early histological study of SD demonstrated the presence of lymphocytes within lesions (335), and this was confirmed later when they were identified as mainly Th CD4-positive cells (51). Langerhans' cell numbers were not increased in lesional skin, and HLA-DR expression on keratinocytes was noted only infrequently (51). An extensive study recently found the infiltrate to consist of lymphocytes, macrophages, monocytes, and Langerhans' cells, with a few granulocytes (131).…”
Section: Cellular Immune Responsesmentioning
confidence: 89%
“…Many groups have found no differences in IgG titers to Malassezia between patients with SD and controls despite studying larger numbers of subjects (49,51,176,219).…”
Section: Seborrheic Dermatitis and Dandruffmentioning
confidence: 99%
“…In peripheral blood from a high number of patients with seborrheic dermatitis, we found an increase in the number of natural killer cells and decreased phytohemagglutinin and concanavalin A stimulation (29,30).…”
Section: Pityrosporum Folliculitismentioning
confidence: 95%
“…The lack of association with hay fever suggests that the eczema predictive of subsequent cervical cancer occurs both in atopic and non-atopic women. This may be seborrhoeic eczema, which is possibly due to an inability to control yeast colonisation and individuals with this type of eczema may have depressed T-cell function (Bergbrant et al, 1991).…”
Section: Discussionmentioning
confidence: 99%